Quality environment 5S enhance service performance: a case study in Malacca State Government - Abdul Rahman, Siti Hajar (2013)
To be successful, organizations must look into the needs and wants of their customers. That is the reason why many researchers and academicians have continuously emphasized on the importance of customer satisfaction. Customer satisfaction is important because many researches have shown that customer satisfaction has a positive effect on an organization's reputation for non-profit organization. Due to this, the consequences of customer satisfaction and dissatisfaction must be considered. Quality Environment (SS) Practice is a concept which can be applied in the workplace by workers. It creates a more conducive, clean and tidy workplace. Customers will feel happy if they got comfortable feeling and safe during delivering services. If all workers implement Quality Environment SS as a daily activity, work definitely become faster and easier. In sustaining SS Practice as a work culture, the organization requires practical initiative to move their employees. This study carried out by researcher is to develop an understanding about the impact of Quality Environment SS Enhance Service Performance in Malacca State Government. It shows on how organizations have successfully implement Quality Environment give impact to organization in productivity, cost, and delivery service related to enhance the Service Performance.